Peran Mediasi Partisipasi Masyarakat dalam Pengaruh Kompetensi Aparatur dan Tranparansi terhadap Akuntabilitas Pengelolaan Dana Desa - Fitra, Halkadri; Agustin, Henri; Mulyani, Erly; Taqwa, Salma; Halmawati, Halmawati (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the influence of apparatus competence and transparency in village fund management on the accountability of village fund management, with community participation as a mediating variable. Community participation is included as a mediating variable because the active involvement of village residents in the planning, implementation, and evaluation of village programs is believed to strengthen the relationship between competence and transparency with accountability. This study employs a quantitative approach using a survey method involving village fund financial management officials, with a total sample of 86 respondents. The data were analysed using path analysis techniques to test both the direct and indirect relationships among the variables. The results of the direct relationship analysis show that the apparatus competence variable does not have a significant effect on community participation, but it does have a positive and significant effect on the accountability of village fund management. Meanwhile, transparency has a positive and significant effect on both community participation and the accountability of village fund management. In addition, community participation has a positive and significant effect on the accountability of village fund management. For the indirect relationship, the results indicate that community participation does not mediate the relationship between apparatus competence and the accountability of village fund management. However, community participation has a positive and significant mediating effect in the relationship between transparency and the accountability of village fund management.